A comparative study on microstructure and mechanical properties of HG785D steel joint produced by hybrid laser-MAG welding and laser welding. (August 2020) - Liu, Fuyun; Tan, Caiwang; Gong, Xiangtao; Wu, Laijun; Chen, Bo; Song, Xiaoguo; Feng, Jicai
Highlights: Hybrid laser-MAG welding and laser welding were used to weld HG785D steel. Different cooling rate led to difference of microstructure in both welded joints. Grain size and microstructure types explain difference in mechanical properties. Heat source melting efficiency of HLAW is larger compared to LBW. Abstract: Hybrid Laser-arc welding (HLAW) and laser beam welding (LBW) of HG785D steel were investigated by comparing microstructure, mechanical properties and heat source melting efficiency. Same microstructure of lath martensite (LM) was observed in fusion zone (FZ) of the two welded joints. However, coarser grain size and more random crystallographic orientations of FZ in HLAW joint were investigated via electron back-scatter diffraction (EBSD) analysis. M-A constituent and equiaxed ferrite (EF) were observed in finer-grain HAZ of HLAW joint, whereas fine martensite was obtained in LBW joint. More M-A constituent and granular bainite (GB) appeared in coarse-grain HAZ of HLAW joint. Higher heat input and lower cooling rate of HLAW compared to LBW resulted in presence of different microstructure. All the tensile specimen in both cases fractured at the base metal, while distinct difference in microhardness and low-temperature impact property was observed. Lower microhardness and higher impact energy of fusion zone were obtained in HLAW joint. Moreover, heat source melting efficiency of HLAW for 6-mm-thick HG785D steel plate could be improved by 26% compared to LBW.